Innovations in quality apprenticeships for high-skilled manufacturing jobs in the United States at BMW, Siemens, Volkswagen - Aring, Monika [Verfasser] (My University, 2014)
"This paper investigates quality apprenticeship in three German companies (BMW, Siemens and Volkswagen) that initiated apprenticeship programmes in the states of North Carolina, South Carolina and Tennessee in the southern part of the U.S. The report highlights the strong involvement of the three companies and their active cooperation with community colleges and municipalities in training apprentices in mechatronics, an interdisciplinary area of engineering that combines mechanical and electrical engineering with a high content of computer skills and software knowledge. The ILO case studies examine the effectiveness of apprenticeships in closing the skills gaps, document key aspects of the public and private partnerships that created the apprenticeship programmes, assess the economic arguments for apprenticeship systems, summarize results for both young people and employers, and identify lessons for initiating apprenticeship systems elsewhere." (Editor, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 3.2.2 Großunternehmen; I 2.3.2 Nordamerika; Betriebliche Berufsausbildung; Qualität; Public-private-Partnership; BMW; Siemens; VOLKSWAGEN; USA; Fallstudie